الفجوة بين خريجي الجامعة ومتطلبات سوق العمل (خريجو اللسانيات والترجمة من قسم اللغة العربية بجامعة جنوب شرقيّ سريلانكا أنموذجا): The Gap between the Graduates of the University & the Labour Market Requirements (Graduates of Linguistics & Translation of Department of Arabic Language, South Eastern University of Sri Lanka as a Sample) - Mohamed Haneefa Abdul Munas; Akmal Khuzairy Bin Abd. Rahman; Abdul Rauff Mohamed Mahsoom (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
ملخص هدفت الدراسة الحالية إلى تحليل الفجوة وأسبابها بين خريجي اللسانيات والترجمة من قسم اللغة العربية في جامعة جنوب شرقي سريلانكا وبين متطلبات سوق العمل من وجهة نظر خريجي الجامعة. فسعيا إلى تحقيق هذه الأهداف، فإنّ الباحثِين قد اعتمدوا على المنهج الاستقرائي، والمنهج الوصفي، والمنهج التحليلي. أما تحليل البيانات التي جممت من عينة الدراسة (32 خريجا) كيفيًّا وكمّيًّا فهو من خلال برنامج الحزمة الإحصائية للعلوم الاجتماعية SPSS تحليلاً وصفيًا استدلاليا إحصائيا. فقد خَلَصَت الدراسة إلى وجود الفحوة بين خريجي وحدة اللسانيات والترجمة وبين متطلبات سوق العمل من وجهة نظر الخرجين فيها. وذلك يرجع إلى عدم مناسبة المنهج الدراسي ساري المفعول مع المعيار المعترف به دوليا من جهة، وعدم حصول الطلاب على التدريب العملي الكافي والملائم لمتطلبات سوق العمل. ومن جهة أخرى إلى ضعف كفاءة الطلاب اللغوية التي يَتطلّبُها سوق العمل الحالي من الخرّجين. ويرجو الباحثون من المهتمين إعادة النظر في المنهج الدراسي وتصميمَه حسب المعيار الوطني والدولي مع المشاركة الفعالة من خبراء هذا المجال، وأوصت الدراسة كذلك بضرورة التدقيق في عملية قبول الطلبة والتحاقهم بالتخصص وإعادة تقييمهم بشكل نقدي للتأكد من أهليتهم لمواصلة البكالوريوس المتخصصة في اللسانيات والترجمة. ولعلّ هذه الدراسة تلعب دورا فعّالة في إيجاد الآليات التي تُعين أصحاب القرار على التغلّب على الفجوة السائدة بين هذا الطرفين. Abstract This study aims to analyze employability of the graduates of the linguistics and translation of Department of Arabic Language, South Eastern University of Sri Lanka. It attempts to answer an important question: do the graduates meet the demands of the labor market? Following a vigorous thematic analysis of the qualitative perceptions of the selected graduates, the study finds that there is a widening gap between the skills of the graduates and the expectations of the labor market. The paper identified several reasons for that phenomenon through critically analyzing the available data. As such, firstly, the graduates perceive that overall curriculum of the course, under which they were trained, is not compatible with the national and international standards. Secondly, the course does not focus enough on providing its students with the required level of practical training in this field of study. Thirdly, they highlighted that natural incompetency of the graduates in terms of grasping the linguistic skills also prevents some from meeting the demands of labor market. Based on the analysis, finally, the paper suggests that existing curriculum needs to be improved in line with the national and international standards and the Department should incorporate the experts of the field in that process. and this paper further recommends that student recruitment process for this course must be further scrutinized and critically reevaluated to ensure that only those who are competent, are allowed to enroll in the course.